Selective synthesis of N-unsubstituted and N-arylindoles by the reaction of arynes with azirines - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; "Jain, Shailja"; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2016)
The transition-metal-free and temperature-dependent highly selective reaction of arynes with 2H-azirines allowing the synthesis of either N-unsubstituted or N-arylindoles has been developed. At 60 degrees C, arynes generated from 2-(trimethylsilyl)aryl triflates smoothly insert into 2H-azirines to form 2,3-diarylindoles with high selectivity. Interestingly, when the reaction was performed at -10 degrees C, the selectivity was switched to the formation of 1,2,3-triarylindoles in good yields.